Pierwsza rocznica oswobodzenia Gdańska. - Liga Morska (1944-1953). (Gdańsk : Liga Morska, 1946)
Karta pocztowa.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- karty pocztowe